Gastronomic tourism, protected designations of origin and rural development in Andalusia: present situation - Genoveva Millán Vázquez De La Torre, Emilio Morales Fernández, Leonor M. Pérez Naranjo (Boletín de la Asociación de Geógrafos Españoles)
Resumen